Controlled release of tyrosol and ferulic acid encapsulated in chitosan–gelatin films after electron beam irradiation. (January 2016) - Benbettaïeb, Nasreddine; Assifaoui, Ali; Karbowiak, Thomas; Debeaufort, Frédéric; Chambin, Odile
Abstract: This work deals with the study of the release kinetics of antioxidants (ferulic acid and tyrosol) incorporated into chitosan–gelatin edible films after irradiation processes. The aim was to determine the influence of electron beam irradiation (at 60 kGy) on the retention of antioxidants in the film, their release in water (pH=7) at 25 °C, in relation with the barrier and mechanical properties of biopolymer films. The film preparation process coupled to the irradiation induced a loss of about 20% of tyrosol but did not affect the ferulic acid content. However, 27% of the ferulic acid remained entrapped in the biopolymer network during the release experiments whereas all tyrosol was released. Irradiation induced a reduction of the release rate for both compounds, revealing that cross-linking occurred during irradiation. This was confirmed by the mechanical properties enhancement which tensile strength value significantly increased and by the reduction of permeabilities. Although molecular weights, molar volume and molecular radius of the two compounds are very similar, the effective diffusivity of tyrosol was 40 times greater than that of ferulic acid. The much lower effective diffusion coefficient of ferulic acid as determined from the release kinetics was explained by the interactions settled between ferulic acid molecules and the gelatin–chitosan matrix. As expected, the electron beam irradiation allowed modulating the retention and then the release of antioxidants encapsulated. Highlights: Chitosan-gelatin film containing ferulic acid or tyrosol irradiated by electron beam. Synergic effect of antioxidants and irradiation on water barrier and mechanical properties. Ferulic acid crosslinking under irradiation induces higher retention and lower diffusivity. Tyrosol exhibits higher diffusion coefficient and no retention by the gelatin–chitosan network. Irradiation seems to control the release of tyrosol.